Serious Games Model In Diagnosing Visual Perception Problem For Autistic Students - Mohd. Noor, Helmi Adly (UTeM, 2016)
In order to minimize the negative effects of autism in students as well as to overcome future problems, early identification and diagnosis are the solutions to get students on the right road to dealing with the problems related to autism and overcoming them. A systematic manual has been developed and is used to diagnose visual perception problems in autistic students. Nevertheless, the technique to diagnose visual perception problems in autistic students is manually employed and the hands-on technique is utilised. This study aims to develop Vi-per games as a tool for special education teachers to diagnose visual perception problems in autistic students. These diagnostic tools can assist and help teachers to diagnose their students without the teachers needing to have any experience and knowledge of diagnosing visual perception. A model of serious games to enable diagnosis of visual perception problems was used in this research. Studies have shown that using games has many benefits and helps autistic students. However, none have yet been developed to diagnose visual perception problems in autistic students. In this research, the objectives are to propose a model for visual perception diagnosis by using serious games for autistic students, to propose a new serious game, namely Vi-Per games for diagnosing visual perception, to measure the accuracy of Vi-Per Games diagnosis results and generate a set of comprehensive and systematic reports in order to evaluate the visual perception problems of autistic students, and to obtain the perception of teachers towards the use of the Vi-Per Games. The participants were autistic students and special education teachers from SMK Bandar Baru UDA and SMK Tun Syed Nasir Ismail, both schools in Johor Bahru, Malaysia. The main participants were ten (10) special education teachers who participated in the questionnaire procedures. Ten (10) autistic students from special education classes were selected using pre-test and post-test procedures. The experiment measured the accuracy of using the developed serious games and to obtain the perception of the teachers towards the use of the games for diagnosing visual perception problems in autistic students. The results positively show that the use of Vi-Per Games can help teachers diagnose visual perception problems in autistic students and can replace manual and conventional tests. In addition, the measure of accuracy test was found to be accurate. Overall, the findings show that using the serious game approach effectively engages autistic students as compared to using the conventional approach. The use of Vi-Per Games successfully assists and facilitates teachers in the diagnosis of visual perception problems in autistic students, as compared to the conventional methods of diagnosis. Diagnosing visual perception using serious games gives teachers and students an enjoyable experience in a way that no other medium can offer.